Relevance of Saint DaduDayal in current political field: संत दादूदयाल की वर्तमान राजनीतिक क्षेत्र में प्रासंगिकता - Chhipa, Sunil Kumar (RESEARCH REVIEW International Journal of Multidisciplinary, 2022)
With the defeat of Prithviraj Chauhan in the Second Battle of Tarain in 1192 AD, the establishment of Islamic power in India and the end of Hindu rule occur simultaneously. It was the final end of the process of complete disconnection from the secular basis of Hindushahi in central politics, not merely the defeat of one empire by another. It is a general political principle that any king or ruler becomes popular only by his public welfare works and gets the collective loyalty and participation of the class ruled by him. On the contrary, when the ruling class starts governing with the help of oppressive military power only, starts doing anti-people work, then it becomes the shelter of the public's distaste, hatred, alienation and feeling of alienation. The history of India is full of such examples that the rulers who followed their real religion and treated all the people as equal and worked for their welfare, they became very popular among the people, whereas the rulers who were fanatics and forcefully changed their religion to the people. When compelled to accept or carried out other similar anti-religious, anti-social actions, then both common people and saints stood up as their retaliation. Abstract in Hindi Language: 1192 ई॰ में तराईन के द्वितीय युद्ध में पृथ्वीराज चैहान की पराजय के साथ ही भारतवर्ष में इस्लामी सत्ता की स्थापना और हिन्दू शासन का अंत एक साथ घटित होता है। यह एक साम्राज्य द्वारा दूसरे साम्राज्य की पराजय मात्र न होकर केंद्रीय राजनीति में हिन्दूशाही के लौकिक आधार से पूरी तरह कट जाने की प्रक्रिया का अन्तिम छोर था। यह एक सामान्य राजनीतिक सिद्धान्त है कि कोई भी राजा या शासक अपने जन-कल्याणकारी कार्यों से ही लोकप्रिय बनता है और अपने द्वारा शासित वर्ग की सामूहिक वफादारी और सहभागिता प्राप्त करता है। इसके विपरित जब शासक वर्ग केवल दमनकारी सैनिक शक्ति की सहायता से शासन संचालित करने लगता है, प्रजा विरोधी कार्य करने लगता है तब वह जनता की अरूचि, वितृष्णा, परायेपन और विलगाव की भावना का आश्रय बनता है। भारतवर्ष के इतिहास में ऐसे उदाहरण भरे पड़े है कि जिन शासकों ने अपने वास्तविक धर्म का पालन कर समस्त जनता को एकसमान मानकर उसके हित-साधन के कार्य किये, वे जनता के बीच अत्यधिक लोकप्रिय हुए वहीं जिन शासकों ने धर्मान्ध होकर बलपूर्वक जनता को अपना धर्म ग्रहण करने पर बाध्य किया या अन्य इसी प्रकार के धर्म विरोधी, समाज विरोधी कार्यों को अंजाम दिया तब सामान्य जन और संत मत दोनों उनके प्रतिकार स्वरूप उठ खड़े हुए। Keywords: राजनीतिक परिस्थितियाँ, साम्प्रदायिक सद्भाव, धर्मनिरपेक्षता, लोकतांत्रिक शासन।